Evaluation of serum urea, uric acid and creatinine in OSMF patients: A clinical and biochemical stusdy - Swati Verma; Rahul R Bhowate (Wolters Kluwer Medknow Publications, 2022)
Introduction: Oral submucous fibrosis (OSMF) is described as a chronic debilitating disease of the submucosal tissue. Leaching out compounds from areca nut is the main etiology for OSMF. Biochemical examinations have concentrated on demarcating changes in the blood, serum, or tissues of patients with this disease. Such examinations have given insights into the possible pathogenesis of OSMF. Aim: Estimation of serum urea, uric acid (UA), and creatinine (Cn.) in OSMF patients. Objective: To estimate the level of serum urea, UA, and Cn. in OSMF patients and compare them with habitual betel nut chewers. Materials and Methods: The purposive samples were selected from patients attending the OPD of the Oral Medicine and Radiology (OMR) Department. In total 180 patients were included and divided into three groups. Group I-Patients suffering from OSMF, Group II-Habitual control, and Group III-Healthy control. Results: The mean value of serum UA (mg/dL) in Group I was 7.82 ± 2.18, Group II was 5.83 ± 1.22, and Group III was 5.28 ± 1.10. The mean value of serum Cn. (mg/dL) in Group I was 1.05 ± 0.27, Group II was 1.15 ± 0.22, and Group III was 0.72 ± 0.21. One-way analysis of variance (ANOVA) was applied between the groups and significant differences were found for both serum UA and Cn. with P < 0.0001, whereas no significant difference was found for serum urea. Conclusion: It can be concluded from this study that serum urea, UA, and Cn. of OSMF patients should be evaluated for liver and renal involvement and for overall improving the disease prognosis.